Creative formats of the eco-protest movement in contemporary Russia - Kachusov, Ivan Mihailovich; Mel'nik, Natal'ya Borisovna (Конфликтология / nota bene, 2025)
Environmental issues are one of the most frequent subjects of protest activity in modern Russia. Using the examples of Russia's environmental conflicts from 2015 to 2025, the article examines the creative forms of the modern eco–protest movement - performances, art installations, flash mobs, etc. Their distinctive feature is that they affect the subject of conflict indirectly, through symbols and media images. The key features of such actions can be noted for their relative safety in the face of increasing administrative and military pressure on activists, their potential to gain wide media coverage and the ability to bring a local problem to a national or global level. The article describes and classifies the main types of creative environmental actions. The study was carried out using the case study method and is theoretically based on the concept of "protest repertoires", the theory of information agenda formation (agenda-settings), the theory of frames and the concept of environmental justice. The authors conclude that increased repressive pressure on environmental activists in Russia contributes to the expansion of the repertoire of protest activity through creative formats, which are alternative means. Protest expressions are also an important tool for scaling up and resolving the conflict., forming stable protest coalitions and strengthening the social base of the environmental movement. The ecoprotest movement in modern Russia is being transformed into creative forms that are safer; they allow channeling protest sentiments and environmental activity in the field of legality; they strive to attract broad public masses using positive social activity or the power of artistic, symbolic, allegorical; they are focused on expanding the field of conflict by attracting new participants and raising the status of the conflict; They actively use digital tools to create virtual and widely distribute real eco-protest actions.